(untitled) (Economics and region, 2020)
The article proposed the investigating of the effectiveness of the manager’s performance of tasks that require quantitative and qualitative values (especially, that depend on manager time using). Time is precisely the resource that is essential for a manager. And from its distribution, planning, accounting, the effectiveness and achievement of the set goals will depend. Modern specialists who study the issues of management activities have established that it is on how managers allocate time that both personal efficiency and enterprises will depend (regardless of the size of activity, field of activity, number of employees, etc.), because the manager must not only manage his own time, but also his subordinates. It is the manager who deals with the whole assignment, which will determine the criteria for the distribution of time. In a dynamic environment, time management issues become one of the key factors for management success. One of the biggest challenges that most managers face is not only how they can work hard in a competitive environment, but how they maintain balance without feeling empty. It’s not just about achieving goals around the clock. It’s also about the quality of life. In a dynamic business environment, managers of any level play an important role in how they work with ideas and will be able to convey them to their subordinates. It will be necessary to ensure the achievement of the set goals. For this, it will be useful to use the Minto pyramid principle to work with ideas and management documents. This approach was proposed by Barbara Minto for document management at McKinsey. The success of presenting information in a pyramidal way also lies in the fact that the entity is indicated at the beginning, and then everything else. The management activity is a complexly structured process that involves a significant expenditure of mental labor and the need to ensure psychological health. Therefore, in the context of dynamic changes in the administration of working time based on the rules of time management, it allows to optimize not only the management process, but also to increase the labor productivity of both managers and personnel of the enterprise as a whole.